Effect of the Decrease in Luminance Noise Range on Color Discrimination of Dichromats and Trichromats - de Loureiro, Terezinha Medeiros Gonçalves; Brodeur, Ketan; Schade, Genevieve; Brito, Felipe André Costa; Salomao, Railson Cruz; Miquilini, Leticia; Bonci, Daniela Maria Oliveira; Baran, Luiz Claudio Portnoi; Hauzman, Einat; Goulart, Paulo Roney Kilpp; Cortes, Maria Izabel Tentes; Ventura, Dora Fix; et al. (Frontiers in Behavioral Neuroscience, 2018)
Color vision assessment can be done using pseudoisochromatic stimuli, which has a luminance noise to eliminate brightness differences between the target and background of the stimulus. It is not clear the influence of the luminance noise on color discrimination. We investigated the effect of change in the luminance noise limits on color discrimination. Eighteen trichromats and ten congenital dichromats (eight protans, two deutans) had their color vision evaluated by the Cambridge Colour Test, and were genetically tested for diagnostic confirmation. The stimuli were composed of a mosaic of circles in a 5° circular field. A subset of the circles differed in chromaticity from the remaining field, forming a letter C. Color discrimination was estimated in stimulus conditions differing in luminance noise range: (i) 6–20 cd/m2; (ii) 8–18 cd/m2; (iii) 10–16 cd/m2; and (iv) 12–14 cd/m2. Six equidistant luminance values were used within the luminance noise limits with the mean stimulus luminance maintained constant under all conditions. A four-alternative, forced-choice method was applied to feed a staircase procedure to estimate color discrimination thresholds along eight chromatic axes. An ellipse model was adjusted to the eight color discrimination thresholds. The parameters of performance were threshold vector lengths and the ellipse area. Results were compared using the Kruskal-Wallis test with a significance level of 5%. The linear function model was applied to analyze the dependence of the discrimination parameters on the noise luminance limits. The first derivative of linear function was used as an indicator of the rate of change in color discrimination as a function of luminance noise changes. The rate of change of the ellipse area as a function of the luminance range in dichromats was higher than in trichromats (p < 0.05). Significant difference was also found for individual thresholds in half of the axes we tested. Luminance noise had a greater effect on color discrimination ability of dichromats than the trichromats, especially when the chromaticities were close to their protan and deutan color confusion lines.